Worker Saturation in Facing Changes in the Work Environment: The Physiological Impact of Online Jobs - Thongprasom, Napasorn; Pow, Whirathep; Pukklaw, Youyen (Journal of Asian Multicultural Research for Social Sciences Study, 2022)
This article discuss about worker saturation in facing changes in the work environment in the physiological impact of online jobs. During the Covid-19 epidemic, social segregation was implemented, and employees worked from home (WFH) via online platform. Some workers get saturation in facing the situation. A process that makes individuals feel ill, uneasy, or anxious as a result of their employment, workplace, or work circumstance. The capacity to adapt to and appreciate current circumstances transforms stress from distress to eustress. Effective stress management tactics include regular exercise, setting aside time for relaxation and self-care, balancing work and pleasure, and practicing time management and meditation